Mastectomia : significados e repercussões no processo de viver de um grupo de mulheres - Zanin, Sibeli Carla Garbin (2014)
Breast cancer is the most prevalent among women and it is associated with many changes in its bearers lives. Among the consequences thereis fear, suffering, changes in body imageand sexuality. The aim of the study was tounder stand the meanings and the repercussions of mastectomy on women s lives. Exploratory descriptive study with qualitative nature developed with 16 women who had under gone mastectomy in the last three years in two hospitals from the city of Passo Fundo. Data collection was conducted through semi-structured interviews between May and September 2013. This thesis is structured in two scientific productions, the first is a scientific article and brings the result of Field research of the impact of mastectomy on women's lives, structured in to categories such as: meanings of mastectomy, family support, spirituality, body image and sexuality. The seconds cientific production presents a literature review on the topic. The data show that the women in the study gave new meanings to their lives after the experience of mastectomy influencing new ways of thinking and acting